Expression and Function of the Chemokine, CXCL13, and Its Receptor, CXCR5, in Aids-Associated Non-Hodgkin's Lymphoma. (29th July 2010) - Widney, Daniel P.; Gui, Dorina; Popoviciu, Laura M.; Said, Jonathan W.; Breen, Elizabeth C.; Huang, Xin; Kitchen, Christina M. R.; Alcantar, Juan M.; Smith, Jeffrey B.; Detels, Roger; Martínez-Maza, Otoniel
Abstract : Background . The homeostatic chemokine, CXCL13 (BLC, BCA-1), helps direct the recirculation of mature, resting B cells, which express its receptor, CXCR5. CXCL13/CXCR5 are expressed, and may play a role, in some non-AIDS-associated B cell tumors. Objective . To determine if CXCL13/CXCR5 are associated with AIDS-related non-Hodgkin's lymphoma (AIDS-NHL). Methods . Serum CXCL13 levels were measured by ELISA in 46 subjects who developed AIDS-NHL in the Multicenter AIDS Cohort Study and in controls. The expression or function of CXCL13 and CXCR5 was examined on primary AIDS-NHL specimens or AIDS-NHL cell lines. Results . Serum CXCL13 levels were significantly elevated in the AIDS-NHL group compared to controls. All primary AIDS-NHL specimens showed CXCR5 expression and most also showed CXCL13 expression. AIDS-NHL cell lines expressed CXCR5 and showed chemotaxis towards CXCL13. Conclusions . CXCL13/CXCR5 are expressed in AIDS-NHL and could potentially be involved in its biology. CXCL13 may have potential as a biomarker for AIDS-NHL.